From Local to Globe: The Representation of Local Culture in An Undergraduate EFL Students’ Textbook - Humairoh, Mega Fariziah Nur; Riska, Hanum Kurnia (Journal of Language Intelligence and Culture, 2022)
Given the wide variety of circumstances in which English is being used globally, the role of local culture in teaching English as a Foreign Language (EFL) is a challenging one. Based on the sociocultural viewpoint that language use is dynamic and context-dependent, this article is aimed to investigate the insertion of cultural values in the English textbook that is suitable and practical for undergraduate students. This developmental research employed Preffers model which consists of six stages:  Identify the problem, describe the objectives, design & develop the artifact, test the artifact, evaluate testing results, and communicate the testing result.  The sample of this study was 15 students of undergraduate students who is taking the English course. Results of an analysis of six sets of ELT textbooks that are distributed extensively and their cultural content are given. The validity test was done by three expert validators. It demonstrated the mean 86.7 and categorized as valid. Then, the practicality test showed a percentage 76.8% And also categorized as good practicality.  Our result can be concluded that the developed English textbook is suitable, practical and beneficial for students. We further recommend using this textbook for teaching English.